Diagnostic Accuracy of Serum Procalcitonin in Early Onset Neonatal sepsis: A tertiary care experience - Hafsah Naz, Saman Zafar, Neelam Iqbal, Perwez Ali, Arshia Ijaz, Ammara Ijaz Rana (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Early-onset neonatal sepsis (EONS) is a life-threatening condition with nonspecific clinical features and delayed culture results, leading to diagnostic uncertainty. Objective: To evaluate the diagnostic accuracy of serum procalcitonin in early-onset neonatal sepsis and compare its performance with C-reactive protein (CRP) and total leukocyte count (TLC), using blood culture as the gold standard. Methods: This cross-sectional analytical study was conducted at Mayo Hospital Lahore from January 2023 to June 2023. A total of 185 neonates were enrolled in the study. After obtaining informed written consent from parents or legal guardians, clinical history and relevant demographic data were recorded. Under strict aseptic precautions, blood samples were collected before the initiation of empirical antibiotic therapy. Samples were sent for serum procalcitonin assay, C-reactive protein (CRP), total leukocyte count (TLC), and blood culture. Results: Out of 185 neonates, 68 (36.8%) were blood culture-positive. Mean PCT levels were significantly higher in culture-positive cases (4.87 ± 1.6 ng/mL) compared to culture-negative cases (0.91 ± 0.6 ng/mL) (p < 0.001). At a cut-off of ≥2.0 ng/mL, PCT showed 88.2% sensitivity, 84.6% specificity, 77.4% PPV, and 92.3% NPV, with an AUC of 0.89. CRP and TLC demonstrated lower diagnostic accuracy. Elevated PCT levels also correlated with poor clinical outcomes such as the need for ventilation, inotropic support, and mortality. Conclusion: It is concluded that serum procalcitonin is a reliable and early diagnostic marker for neonatal sepsis, outperforming CRP and TLC. Its incorporation into neonatal sepsis protocols may improve early detection, guide clinical decisions, and reduce unnecessary antibiotic use. Keywords: Procalcitonin, Neonatal sepsis, Biomarkers, Diagnostic accuracy, Blood culture, CRP, TLC.